Deep Learning Implementation Strategies in Indonesia National Curriculum: A Culturally Responsive Framework for Pinrang Regency - Pada, Damir; S, Jumadi (Lembaga KITA, 2025)
This research develops implementation strategies for Deep Learning approaches within Indonesia's National Curriculum specifically adapted for Pinrang Regency's educational settings. The study employs descriptive qualitative methodology through document analysis and literature review to create strategic frameworks addressing regional educational challenges while honoring Buginese cultural heritage. Five primary strategic domains emerged: conceptual foundation development integrating